Reinterpretasi Pemikiran Al-Mawardi tentang Gender dan Kepemimpinan dalam Fiqh Siyasah: Studi Kasus Khofifah Indar Parawansa - Maulana, Raihan; Rohmah, Neneng Sobibatu; Millata, Chanifia Izza (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2025)
This article analyses women's leadership in politics through a reinterpretation of Al-Mawardi's thoughts in Ahkam al-Sulthaniyyah, particularly regarding the concept of gender and leadership requirements. The study focuses on the case of Khofifah Indar Parawansa as Governor of East Java. Qualitative method is used with hermeneutic textual analysis of Ahkam al-Sulthaniyyah and Khofifah's performance data. The results of the study show that Al-Mawardi's thoughts, although prioritising men as leaders, can be reinterpreted based on the principle of maslahat in Islam. Khofifah's leadership provides empirical evidence that women can lead well in the context of modern democracy, as long as they fulfil the criteria of justice, capability and benefits for society. This article also shows that the application of the principle of maslahat in fiqh siyasah provides room for women's leadership, as long as it prioritises the benefit of the people and the public interest, without being trapped in gender issues alone.